DESIGN OF SOFT SOIL IMPROVEMENT AND SLOPE REINFORCEMENT FOR EXCAVATION AND EMBANKMENT ON THE JAKARTA â CIKAMPEK II SELATAN TOLL ROAD PROJECT FROM STA 09+775 TO STA 15+000 - Rama Adamas, Nur
Jakarta-Cikampek II South Toll Road Project is a part of the National Strategic Project developed through a collaboration between PT. Jasa Marga and PT. Wiranusantara Bumi. This toll road spans 64 kilometers and is divided into three construction sections: Section 1 (Jatiasih – Setu) covers 9.3 km, Section 2 (Setu – Taman Mekar) covers 24.85 km, and Section 3 (Taman Mekar – Sadang) covers 27.85 km. Based on field investigations, the project faces various geotechnical challenges, such as an 8-meter-high embankment on 17 meters of soft clay soil from STA 09+775 to STA 09+900 and a vertical 90° slope from STA 15+000 to STA 15+125. Soft clay soil has significant issues in road construction due to its low permeability, conducting to long settlement that can severely damage the road structure. Additionally, the high embankment and vertical slope increase the risk of failure, necessitating reinforcement. The proposed method for improving the soft clay soil involves preloading and installing prefabricated vertical drains (PVD) in a triangular configuration with PVD spacing variations of 1 meter, 1.25 meters, and 1.5 meters to expedite consolidation settlement. The results indicate that the consolidation settlement times for these PVD spacings are 183 days, 281 days, and 421 days, respectively. The proposed slope reinforcement method uses geotextile with strengths of 100 kN/m in the upper zone and 150 kN/m in the lower zone. Global stability analysis using PLAXIS 2D shows safety factors of 1.478 for short-term and 1.589 for long-term conditions, meeting the minimum required standards of 1.3 and 1.5, respectively. For the vertical slope, the proposed reinforcement methods are soil nailing and sheet piling. For soil nailing, a rectangular pattern with horizontal and vertical spacing of 1.5 meters and a borehole diameter of 100 mm is planned, with nail bar inclinations of 10°, 15°, and 20°. The design results indicate that this method meets global stability, pull-out failure, tensile failure, shear failure, wall failure, punching shear failure, and facing head stud failure criteria. However, the deflection values do not meet the maximum allowable limit of 4.7 cm, indicating that soil nailing reinforcement does not satisfy the design criteria. For sheet piling, PZ27 steel sheet piles with a driving distance of 457.2 meters and a penetration depth of 9.5 meters are planned. The design results indicate that this method meets global stability, basal heave failure, blow-in failure, and piping failure criteria. However, the deflection values do not meet the maximum allowable limit of 4.7 cm, indicating that sheet pile reinforcement does not satisfy the design criteria.